EFL STUDENTS’ ATTITUDES TOWARD SHORT FILM-BASED JOYFUL LEARNING ACTIVITIES - Saffana Salsabila; Megawati, Fika; Nafidah, Hikmah (Magister Scientiae, 2026)
Learning English needs to be supported by interesting activities and attractive media. One of the most meaningful media to assist students in developing the language component is short films. Therefore, this study aims to analyze the utilization of short films as interactive learning media in improving the English language skills of high school students. The method used is a descriptive qualitative approach with an observation technique conducted for four weeks in one of the high schools in Sidoarjo. Data were collected through direct observation of learning activities, as well as students' reflections on the use of short films in the learning process. The results showed that the utilization of short films significantly increased students' active involvement in English learning. In addition, the use of short films has a positive impact on improving vocabulary acquisition, pronunciation, and listening comprehension. The advantages of short films, such as relatively short duration, contextual and interesting content, and the use of authentic language, support a more interactive, relevant, and meaningful learning process. Thus, short films can be used as one of the effective and innovative learning media to improve students' English language skills. The results of this study are expected to be a reference for educators in designing audiovisual-based learning strategies that are more interesting and in accordance with students' need